Penguatan Literasi Stunting pada Remaja sebagai Upaya Penurunan Prevalensi Stunting di Posyandu Remaja Paal Merah II Kota Jambi - Wulansari, Arnati; Lathifa, Nelda Nur (Jurnal Abdimas Kesehatan (JAK), 2024)
Lack of knowledge among teenagers in the working area of the Paal Merah II Health Center, Jambi City is one of the causes of the stunting problem. The stunting program implemented also involves targeting teenagers as an important period in preparation for giving birth to the nation's next generation. One way to overcome this problem is to strengthen literacy regarding stunting. This activity was a discussion and education activity for teenagers at the stunting locus health center, namely the Paal Merah II health center. The aim of this community service activity is to provide knowledge about the important role of teenagers in preventing and overcoming stunting. This activity was carried out face-to-face and was attended by 17 female students at the Paal Merah II Health Center Posyandu Remaja Jambi City in October 2022-February 2023. The method of implementing the activity was carried out by discussion by forming an activity with the name Discussion and Sharing, abbreviated as "DARING REMAJA". The results of this community service show that 50% of the audience had knowledge in the poor category during the pre-test. The post test results showed an increase in knowledge scores of 20 points. As many as 75% of the audience answered all questions correctly. It can be concluded that after carrying out this activity, teenagers can understand stunting and are willing to participate in the stunting reduction program in Jambi City.